The crystal structure of (R)-2-aminobutanamide hydrochloride, C4H11ClN2O - Wang Fengfeng; Luan Lin; Wang Youyou; Hu Xiaowen; Zhang Caiyu; Liu Yang (Zeitschrift für Kristallographie - New Crystal Structures)
C4H11ClN2O, orthorhombic, P212121 (no. 19), a = 4.9699(1) Å, b = 7.5867(2) Å, c = 17.3719(4) Å, V = 655.01(3) Å3, Z = 4, Rgt(F) = 0.0286, wRref(F2) = 0.0796, T = 200 K.